2020
DOI: 10.1159/000506506
|View full text |Cite
|
Sign up to set email alerts
|

Relapsing and Progressive Complications of Severe Hypertriglyceridemia: Effective Long-Term Treatment with Double Filtration Plasmapheresis

Abstract: Background: Severe hypertriglyceridemia (HTG) is associated with major complications such as acute or relapsing pancreatitis (AP) and atherosclerotic cardiovascular disease (ASCVD). Rapid elimination of triglyceride (TG)-rich lipoproteins (LP) with double filtration plasmapheresis (DFPP) without need for substitution has been found to be effective for the acute, short-term treatment of HTG-induced AP. Data on the long-term use of DFPP to prevent HTG-associated complications are scarce. Objectives: To evaluate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 44 publications
1
12
0
Order By: Relevance
“…21 Grupp et al evaluated the efficacy of long-term regular DFPP in 10 patients for preventing recurrence of hypertriglyceridemia-associated complications. 22 The results of those studies are promising. DFPP can be applied to new diseases based on the accumulated evidence.…”
Section: Commentsmentioning
confidence: 96%
See 1 more Smart Citation
“…21 Grupp et al evaluated the efficacy of long-term regular DFPP in 10 patients for preventing recurrence of hypertriglyceridemia-associated complications. 22 The results of those studies are promising. DFPP can be applied to new diseases based on the accumulated evidence.…”
Section: Commentsmentioning
confidence: 96%
“…Chang et al applied it for 12 patients and another six patients received DFPP for prophylactic purposes 21 . Grupp et al evaluated the efficacy of long‐term regular DFPP in 10 patients for preventing recurrence of hypertriglyceridemia‐associated complications 22 . The results of those studies are promising.…”
Section: Commentsmentioning
confidence: 99%
“…For patients with chronic hypertriglyceridemia (HTG), the goal before the DFPP session was TG <700 mg/dL. The ASFA guidelines recommend the goal of treatment to reduce time‐averaged LDL‐C by >60% from the baseline and selective LA systems are known to reduce LDL‐C levels by >60‐70% after a single session 1,12,14 . Moreover, in our department, patients treated with Tandem HD and DFPP had to undergo lab tests twice a month, before and after each DFPP session to determine the safety of hemoglobin, hematocrit, platelet, albumin (nephelometry) and fibrinogen levels and efficacy with total cholesterol, LDL‐c and TG blood levels.…”
Section: Protocols For Hd or Dfpp And Tandemmentioning
confidence: 99%
“…When chronic treatment is indicated, a semi‐selective (DFPP) or selective TP (adsorption) method might be preferred to non‐selective SPE to avoid the need for long‐term human plasma product substitution. Bosch et al reported the first tandem experiment with HD and the heparin‐induced extracorporeal LDL‐precipitation (HELP) system 11 but none reported tandem with HD and DFPP as DFPP can be used as a long‐term treatment for LA 1,12,13 . Moreover, the tandem procedure with RRT and TP questions the blood line connection system chosen; parallel or sequential (series‐parallel) connections with considerations about maintaining dialysis efficacy which, as suggested by Kaushik et al 8 require evaluation.…”
Section: Introductionmentioning
confidence: 99%
“… 3 The indications for mTPE are mainly related to antibody-mediated diseases, in which the mechanical removal of antibodies mitigates briefly the disease process. 4 Other conditions that benefit from plasmapheresis are familial lipid disorders 5 , 6 and acute liver failure. 7 …”
Section: Introductionmentioning
confidence: 99%